ANALISIS WACANA KRITIS PADA LIPUTAN BBC NEWS BERJUDUL DILEMA IBU KOTA BARU - Hana Aulia; Nadia Anindita Azyani; Toni Heryadi; Tri Saptarini; Nani Darmayanti (tuahtalino, 2021)
This research analyzes the ideology contained in the video footage of BBC NEWS coverage of the dilemma of the new capital which was uploaded on March 6, 2020 on the BBC News youtube channel. The purpose of this study is to describe micro, meso, and macro analysis in the discourse of the new capital city presented by BBC News. This study uses the basic theory of critical discourse analysis combined between Theo van Leeuwen's model which focuses on micro aspects, namely discourse production using inclusion and exclusion strategies and Norman Fairclough's model on meso and macro analysis. The results of the analysis on the micro aspect with the use of exclusion and inclusion strategies in the discourse show the dominance of the inclusion of actors, namely the indigenous people of Kalimantan and environmental activists as victims of government policies in terms of relocating the capital city. The meso aspect analysis shows that the whole discourse production process was created and compiled by the BBC News team based on the results of field observations and interviews. The production team also showed more contra voices by including more counter arguments in the dialogue and narrative. The strategy for distributing discourse through the YouTube channel was chosen because the issue raised is an important issue and is currently being discussed nationally. The macro analysis shows the relationship that the BBC News coverage related to the issue of relocating the capital city to Kalimantan is about the majority of people in Kalimantan who are contradicting the issue of relocating the capital city.